Reproductive Factors, Use of Exogenous Hormones, and Pancreatic Cancer Incidence: The Norwegian Women and Cancer Study - Alvarez,Antoine; Benjaminsen Borch,Kristin; Rylander,Charlotta (Clinical Epidemiology, 2021)
Antoine Alvarez,1 Kristin Benjaminsen Borch,2 Charlotta Rylander2 1Faculty of Medicine, Paris-Sud University, Paris, France; 2Department of Community Medicine, Faculty of Health Sciences, UiT The Arctic University of Norway, Tromsø, NorwayCorrespondence: Charlotta RylanderDepartment of Community Medicine, Faculty of Health Sciences, UiT The Arctic University of Norway, Tromsø, 9037, NorwayTel +47-77-644-831Email charlotta.rylander@uit.noIntroduction: The incidence of pancreatic cancer is increasing worldwide and characterized by a particularly low survival rate. Studies have reported weak and inconsistent evidence for associations among reproductive factors, use of exogenous hormones, and pancreatic cancer incidence in women.Purpose: To investigate relationships between reproductive factors, exogenous hormones, and the rate of pancreatic cancer incidence in a large population-based prospective cohort of women in Norway.Methods: We used data from the Norwegian Women and Cancer study on 588 incident cases of pancreatic cancer diagnosed among 165,419 women, with mean follow-up of 18.7 years. Cox proportional-hazard models were used to estimate HRs and 95% CIs for associations of interest.Results: Cumulative breastfeeding duration > 24 months was associated with 63% decreased incidence of pancreatic cancer compared to no breastfeeding. We observed an inverse linear dose–response trend between cumulative breastfeeding duration and pancreatic cancer incidence, which was confirmed in parous women and ever-smokers. Higher age at first birth and menopause were inversely associated with pancreatic cancer incidence, though with less precise effect estimates. Current use of oral contraceptives was associated with a doubling of pancreatic cancer incidence, but the analysis was hampered by a small number of cases. There was no evidence of any associations between age at menarche, parity or use of menopausal hormone therapy, and incidence of pancreatic cancer.Conclusion: Our results suggest a potential protective effect of ...